Does The Declaration of The Covid-19 Occurrence in Indonesia Affect Abnormal Return and Trading Volume Activity? Research on Jakarta Islamic Index - Haryono, Caroline Bella Charist; Husaini, Ahmad (Universitas Batanghari Jambi, 2024)
The Coronavirus, which causes the disease outbreak known as Covid-19, spreads rapidly over the world and attacks the human respiratory system. The Covid-19 in Indonesia on March 2, 2020 has been confirmed by the Indonesian government. The financial market has been impacted by this situation, and stock markets worldwide have declined. The aim of this investigation is to ascertain whether a noticeable discrepancy exists between abnormal return and trading volume activity on the Jakarta Islamic Index (JII) both prior to and subsequent to the declaration of Covid-19 in Indonesia. The results derived from this examination demonstrate that the statistical significance of the Difference Test, which examines the abnormal return on the Jakarta Islamic Index (JII) both prior to and subsequent the Covid-19 announcement in Indonesia, is observed to be 0.024, which is less than the conventional alpha level of 0.05. Furthermore, The statistical significance level of the Difference Test in relation to the trading volume activity on the Jakarta Islamic Index (JII) prior to and following the Covid-19 announcement in Indonesia has been determined to be 0.009, which is less than the commonly accepted threshold of 0.05. The inference that can be drawn from this investigation is that there exist notable discrepancies in the abnormal return and trading volume activity on the Jakarta Islamic Index (JII) prior to and subsequent to the disclosure of Covid-19 in Indonesia.